The effect of four weeks of long-term endurance training with and without propolis supplementation on serum levels of Betatrophin/ANGPTL8 in male athletes - Rashvand, F.; Irandoust, K.; Taheri, M.; Khoei, S. G.; Gheibi, N. (Asian Journal of Sports Medicine, 2022)
Background: Betatrophin/angiopoietin-like protein (ANGPTL8) is defined as an adipokine that regulates blood glucose and triglyceride levels. Objectives: This study aimed to evaluate the effect of propolis supplementation for the first time on serum levels of the hormone betatrophin, as a drug target in the treatment of dyslipidemia, in male endurance athletes for four weeks. Methods: 44 male athletes with an average age of 22 ± 3 years, a height of 177.5 ± 6.5 cm, and a weight of 76 ± 6 kg were selected in Qazvin. They were randomly divided into four groups: Supplementation, placebo, physical activity, and control. The supplementation and placebo groups received two 500 mg tablets of propolis and cellulose (in terms of shape and color, are similar to the original supplement and have no properties, flavor, and aroma) once after lunch and once after dinner, respectively. The drug treatment lasted for four weeks. The athletes' weight and serum levels of betatrophin were measured at the beginning and the end of 4 weeks of treatment. The ELISA method was used to assess the serum concentration of betatrophin. Analyzes were performed by the ANCOVA method. Results: The results showed that the long-term endurance training plus propolis supplementation would result in significant changes in the betatrophin serum levels and weight in participants (P = 0.001), but in the athletes without supplementation, these changes were not significant (P > 0.05). Conclusions: The results indicated that betatrophin serum levels in endurance athletes are increased by propolis supplementation, and their weight is decreased.